Trisomy 8 syndrome owing to isodicentric 8p chromosomes: regional assignment of a presumptive gene involved in corpus callosum development. Issue 3 (March 1994) - Digilio, M C; Giannotti, A; Floridia, G; Uccellatore, F; Mingarelli, R; Danesino, C; Dallapiccola, B; Zuffardi, O
Abstract : Two patients with trisomy 8 syndrome owing to an isodicentric 8p;8p chromosome are described. Case 1 had a 46, XX/46, XX, -8, +idic(8)(p23) karyotype while case 2, a male, had the same abnormal karyotype without evidence of mosaicism. In situ hybridisation, performed in case 1, showed that the isochromosome was asymmetrical. Agenesis of the corpus callosum (ACC), which is a feature of trisomy 8 syndrome, was found in both patients. Although ACC is associated with aneuploidies for different chromosomes, a review of published reports indicates that, when associated with chromosome 8, this defect is the result of duplication of a gene located within 8p21-pter. Molecular analysis in one of our patients led us to exclude the distal 23 Mb of 8p from this ACC region.